Nitrogen Fixation And Ammonium Ion Production By Endophytic Bacteria Associated With Tropical Pastures (Journal of Namibian Studies : History Politics Culture, 2022)
The objective of this study was to evaluate the efficiency of endophytic bacteria with potential activity for nitrogen fixation and ammonium ion production associated with different tissues of kikuyo grass in the Colombian Caribbean. Endophytic bacteria from different kikuyo grass tissues were isolated, and the population density was determined in CFU/g of tissue. Each isolated was used to quantitatively and qualitatively evaluate the BNF and evaluate the production of ammonium ion from nitrogen fixation. The bacteria that showed this activity were sequenced for identification of the 16S rDNA gene for eubacteria at the sequence level. 98 isolated of endophyte bacteria from different kikuyo grass tissues were isolated of which 17 were able to produce ammonium ion from nitrogen fixed in vitro. The results of the sequencing showed the presence of a high percentage of similarity with the bacterial species Serratia marcescens, Enterobacter cloacae and Bacillus cereus reduction of N2 to ammonium and becomes a biological resource for nitrogen fixation in the foliage of kikuyo grass in the department of Sucre and a bio-input of microbiological origin for livestock producers and the agrosostainable production of this pasture.